Pola Dasar Perkembangan Pemikiran Islam di Kawasan Melayu - Syam, Syamsuarni; Halimah; M. Fahsul Fuadi; Muhammad Faisal (GHIROH, 2026)
Research on Islamic thought in the Malay world has been shaped through a gradual and contextual historical process, involving a dynamic interaction between Islamic teachings, local cultural traditions, and social developments. The moderation, adaptability, and accommodativeness of Malay Islamic thought provide a distinctive intellectual identity compared to Islamic thought traditions in other regions. This article aims to examine the basic patterns of Islamic thought development in the Malay world and analyze its implications for Islamic education management practices. This research uses a qualitative approach with a literature study method through a critical review of primary and secondary sources relevant to the study of Islamic thought and Islamic education in the Malay world. The research findings indicate that Malay Islamic thought developed through an integrative pattern between Islamic values ​​and local culture, strengthening the Ahlussunnah wal Jama'ah tradition, and a moderate attitude in responding to the dynamics of modernization. This pattern has direct implications for Islamic education management, particularly in the development of educational leadership, curriculum design, and institutional governance that emphasizes the principles of moderation, balance, and sustainability.